Quality Analysis of English Subtitles in Indonesian YouTube Video using Appraisal Theory - Efraim Aero; Safrina Noorman (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
This research aims to assess the quality of English subtitle in several video blogs (vlogs) made by Indonesian YouTube content creators. Subtitle can be described as words that translate what the speaker is saying in a video into a different language and subtitle usually appear at the bottom of the screen. Subtitle holds important roles in digital era. Subtitle helps content creator to convey contents of their vlogs.  Subtitle also able to help viewer who are deaf or having difficulties with hearing so they can enjoy the vlog. Subtitle also able to help content creator reach out to global audience. Indonesian content creator usually provides English subtitle on their vlog to aim global YouTube viewer. Subtitling is not an easy process. Subtitling involves a shift from oral to written. Subtitling involves linguistics aspect and is the reason such research exists. Linguistic aspect such as appraisal theory is needed to assess the quality of subtitle. This research aims to identify quality of English subtitle which contains appraisal system. The data of this research were teken from vlogs and it were collected through library research. This research classified as descriptive qualitative research. The result of this study shows that some Indonesian content creator still need some quality improvement of its subtitle.